Perivascular Epithelioid Cell Tumor: A Case Report of a Rare Entity - Cardosa, MF (2021)
Perivascular epithelioid cell tumor is a rare mesenchymal tumor with myomelanocytic differentiation. It mainly occurs in middle-aged females and can be found at any location. The differential diagnosis is broad but the immunohistochemical biomarkers establish the diagnosis. A 4-year-old girl was referred to a pediatric gastroenterology clinic due to recurrent umbilical pain and the workup revealed biliary lithiasis. She remained in follow-up, asymptomatic, no physical findings, and stable ultrasound. Six years later, a supra-umbilical mass was detected by ultrasound, and the magnetic resonance imaging revealed a highly vascularized intraperitoneal tumor with well-defined limits. Surgical mass resection was performed, and the histology revealed morphological and immunohistochemical aspects of a perivascular epithelioid cell tumor of the abdominal wall. Given the size of the lesion (> 5 cm) and admitting uncertain malignant potential, she was submitted to margin enlargement. Four years later, she remains asymptomatic without clinical or imagiological evidence of relapse.